KOMPARASI NILAI KEKERABATAN TANÈYAN LANJHÁNG MASYARAKAT MADURA - Yetti Hidayatillah (Universitas Negeri Malang, 2017)
Abstract: Tanèyan Lanjháng is a residential pattern whose buildings are lined up; lined up from west to east and facing each other between north and south. The feature in the Tanèyan Lanjháng settlement pattern is the clustered building pattern and consists of the main house, kin house, kitchen, cage, and Langghar (small mosque) building and well. The existence of settlement pattern Tanèyan Lanjháng is a manifestation of the symbols of kinship, rope brotherhood, and a sense of solidarity between families and relatives who are intertwined in a bond of bloodline either from the relationship of blood or through marriage bonds. This research uses qualitative approach method. The results of this study indicate that the Comparison of Kinship Values between Karang Cempaka and Serah Tengah Villages is seen in the pattern of settlements occupied by families and relatives of Tanèyan Lanjháng. In such a settlement pattern (Tanèyan Lanjháng), the researcher found some similarities and differences between these two villages. The similarities are found in the settlement patterns of the Tanèyan Lanjháng family, the kinship, the layout of the kitchen and enclosure, the shape of the house, and their marriage customs. Meanwhile, the difference is seen in the Tanèyan form, the layout of the cage building, the number of house buildings inhabited by families and relatives, problems or conflicts that occur among families, the role of figures Tanèyan Lanjháng, as well as changes in the buildings of langghár and wellAbstrak: Tanèyan Lanjháng adalah pola pemukiman yang bangunannya berjejer, berderet yang dibangun dari barat ke timur dan saling berhadapan antara utara dan selatan. Ciri dalam pola pemukiman Tanèyan Lanjháng adalah pola bangunan yang berkelompok dan terdiri dari rumah induk, rumah kerabat, dapur, kandang, dan bangunan Langghár serta sumur. Adanya pola pemukiman Tanèyan Lanjháng ini merupakan wujud dari simbol kekerabatan, tali persaudaraan serta rasa solidaritas yang tinggi antar para keluarga dan kerabat yang terjalin dalam suatu ikatan garis keturunan baik itu dari hubungan darah maupun melalui ikatan perkawinan. Kajian ini menggunakan pendekatan kualitatif. Komparasi Nilai Kekerabatan Antara Desa Karang Cempaka dan Desa Serah Tengah, terlihat pada pola pemukiman yang dihuni oleh para keluarga dan kerabat Tanèyan Lanjháng. Dengan adanya pola pemukiman Tanèyan Lanjháng ini, peneliti menemukan bentuk persamaan dan perbedaan antara kedua Desa ini. Persamaannya ditemukan pada pola pemukiman keluarga Tanèyan Lanjháng, tali kekerabatan, tata letak bangunan dapur dan kandang, bentuk rumah, dan adat perkawinan mereka. Sementara untuk perbedaannya terlihat pada bentuk Tanèyan, tata letak bangunan kandang, banyaknya bangunan rumah yang dihuni oleh keluarga serta kerabat, masalah atau konflik yang terjadi di antara keluarga, adanya peran tokoh Tanèyan Lanjháng, serta perubahan bangunan langghár serta sumur DOI : http://dx.doi.org/10.17977/um019v2i22017p146